Atomic layer deposited tantalum oxide to anchor Pt/C for a highly stable catalyst in PEMFCs. Issue 20 (5th May 2017) - Song, Zhongxin; Wang, Biqiong; Cheng, Niancai; Yang, Lijun; Banham, Dustin; Li, Ruying; Ye, Siyu; Sun, Xueliang
Abstract : Pt/C catalysts with high stability can be realized by selective-area atomic layer deposition of TaO x anchors. Abstract : Tantalum oxide (TaO x ) nanoparticles (NPs) are deposited on a commercial Pt/C catalyst by an area-selective atomic layer deposition (ALD) approach to enhance the stability of the catalyst in proton exchange membrane fuel cells (PEMFCs). Due to the application of a blocking agent for protecting the Pt surface, TaO x particles are selectively nucleated and grown around Pt NPs. The TaO x loading on the Pt/C surface could be controlled precisely by varying the number of ALD cycles. When deposited on the Pt/C surface with 35 ALD cycles, the TaO x -anchored Pt NPs formed an excellent triple-junction structure of TaO x –Pt–carbon. The electrochemical durability tests indicated that the TaO x -anchored Pt/C catalyst showed comparable catalytic activity and superior long-term stability to Pt/C. Moreover, the long-term stability test in membrane electrode assembly (MEA) indicated a very low power density loss (12%) after a 120 h accelerated durability test. The significantly enhanced catalyst stability during PEMFCs operation is due to the anchoring effect of TaO x via strong metal oxide–support interactions. This strategy shows great potential for developing highly stable catalysts for PEMFCs.